2021
DOI: 10.1038/s41598-021-92980-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of choroidal thickness measurements between spectral domain optical coherence tomography and swept source optical coherence tomography in children

Abstract: Choroidal thickness is associated with many ocular conditions, interchangeability among different generations of optical coherence tomography is therefore important for both research purpose and clinical application. Hence, we compared choroidal thickness measurements between spectral-domain optical coherence tomography (SD-OCT) and swept-source optical coherence tomography (SS-OCT) in healthy paediatric eyes. A total of 114 children from the population-based Hong Kong Children Eye Study with mean age of 7.38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Tan et al, however, reported differences between automated and manual ChT measurements between SS-OCT and SD-OCT, which could not be eliminated [36]. Lee et al found significant inter-device differences in ChT analysis in children, and that these measurements were not interchangeable [37]. Automated and manual segmentation methods for ChT may be interchangeable however, in healthy eyes, with automated methods being preferred and having more value in large scientific clinical research and routine patient assessment [38].…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al, however, reported differences between automated and manual ChT measurements between SS-OCT and SD-OCT, which could not be eliminated [36]. Lee et al found significant inter-device differences in ChT analysis in children, and that these measurements were not interchangeable [37]. Automated and manual segmentation methods for ChT may be interchangeable however, in healthy eyes, with automated methods being preferred and having more value in large scientific clinical research and routine patient assessment [38].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the OCT type was the primary cause of heterogeneity. It is suggested that ChT measured on SS-OCT was 5.9 to 49.3 μm thinner than that on spectral domain OCT, and there was a significant inter-device difference of ChT measurements in normal children [58] . Fontaine et al [35] found that ChT tends to increase from early childhood to adolescence in normal children without refractive errors, peaking in young adulthood, but then decreases with age in older populations.…”
Section: Discussionmentioning
confidence: 91%
“…Owing to its greater scanning depth, SS-OCT (Version 9.31, Topcon Co., Tokyo, Japan) provides an advantage in visualizing the choroid [20][21] . According to previous articles [22] , the retinal and choroidal thicknesses have been defined respectively.…”
Section: Swept-source Optical Coherence Tomography Imagingmentioning
confidence: 99%